Polymers in Nanomedicine - Kunugi, Shigeru; Yamaoka, Tetsuji; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Ernst Wagner Functional Polymer Conjugates for Medicinal Nucleic Acid Delivery Takami Akagi Masanori Baba Mitsuru Akashi Biodegradable Nanoparticles as Vaccine Adjuvants and Delivery Systems: Regulation of Immune Responses by Nanoparticle-Based Vaccine Yuichi Ohya Akihiro Takahashi Koji Nagahama Biodegradable Polymeric Assemblies for Biomedical Materials Yutaka Ikeda Yukio Nagasaki PEGylation Technology in Nanomedicine Kazuhiko Ishihara Yan Xu Tomohiro Konno Cytocompatible Hydrogel Composed of Phospholipid Polymers for Regulation of Cell Functions Yusuke Arima Koichi Kato Yuji Teramura Hiroo Iwata Design of Biointerfaces for Regenerative Medicine Jeremy J. Mercuri Dan T. Simionescu Advances in Tissue Engineering Approaches to Treatment of Intervertebral Disc Degeneration: Cells and Polymeric Scaffolds for Nucleus Pulposus Regeneration Ranu K. Dutta Prashant K. Sharma Hisatoshi Kobayashi Avinash C. Pandey Functionalized Biocompatible Nanoparticles for Site-Specific Imaging and Therapeutics
Keywords: Chemistry; Biotechnology; Polymers; Biochemistry; Biomaterials; Chemistry; Polymer Sciences; Medical Biochemistry; Biomaterials; Biotechnology; Medicinal Chemistry